Mixed management in growing and finishing pigs: Differences between gender and their impacts on behavior, growth performance, and physiological parameters. - Angela Cristina da Fonseca de Oliveira; Leandro Batista Costa; Saulo Henrique Weber; Yuliaxis Ramayo-Caldas; Antoni Dalmau (PLoS ONE, 2023)
Mixing, a common management strategy used to regroup pigs, has been reported to impair individual performance and affect pig welfare because of the establishment of a new social hierarchy after regrouping. In this study we aimed to determine whether mixing management (non-mixed vs. mixed) and gender (gilts vs. barrows) affect the social and non-social behavior, performance, and physiological parameters of pigs. A total of 96 growing pigs (48 barrows and 48 females) were separated into two treatments: control (CT)-pigs that were mixed once during the growing-finishing period; and social stress (SS)-pigs that were mixed thrice during the growing-finishing period. We recorded social and non-social behaviors, injury score, performance, and physiological parameters during the experimental period. Data were grouped by the period, based on each mix performed, and overall values. The statistical analysis performed considered gender and treatment. For treatment, during period-II and III, the SS group presented the highest frequency of agonistic interactions (AI), stayed longer lying laterally (LL) and sternly (LS), and explored more enrichment material (ER) than the CT group. Furthermore, SS pigs presented the highest injury score in the ear, head, and middle and posterior regions. Compared to the females, the barrows spent more time at the electronic feed station and initiated most of the agonistic interactions during period-II, and they presented a higher injury score for the ear and head regions during period-III. In conclusion, repeated regrouping significantly affected social and feeding behavior without severely altering performance and physiological parameters. Furthermore, different patterns of social and feeding behavior, agonistic interactions, and injury scores between barrows and females were observed. This study provides an understanding of the impact of mixing management and gender differences on pigs, and this knowledge can be used to improve swine productivity and welfare.